When and how does volunteering influence wages? – Evidence from panel data - Eberl, Andreas; Krug, Gerhard (Acta Sociologica, 2020)
Volunteering is an activity in which individuals work for free to benefit others; however, research has also focused on the benefits volunteers themselves might experience. We add to the literature by focusing on how not only volunteering itself has an impact on wages but how the intensity, duration and timing of volunteering also have an effect on these. In addition, we distinguish between the effects on volunteers in the same job and when changing a job, and test the role of social capital. Using German data from the Socio-Economic Panel, we find that current volunteering has positive effects on wages in a fixed effects wage regression, especially if individuals volunteer with low to medium intensity. The duration of volunteering does not increase wages. However, based on the dummy impact function, we find that volunteering increases wages almost immediately and that this effect remains fairly constant over time. We find no indication that reverse causality drives this effect. Furthermore, we show that the wage benefits of volunteering are realized only through job changes, not on-the-job wage progression. With regard to job changers, we show that social capital accumulation through volunteering is one reason explaining the observed wage effects.<br
Keywords: Volunteering; social capital; wages; panel data